Accessibility and connectivity – Movement between cities, as a critical factor to achieve success on cross-border cooperation (CBC) projects. A European analysis. (July 2017) - Castanho, Rui Alexandre; Vulevic, Ana; Cabezas Fernández, José; Fernández-Pozo, Luis; Naranjo Gómez, José Manuel; Loures, Luís Carlos
Abstract: Nowadays, cross-border cooperation (CBC) is an undeniable reality in the space encompassed between European borders. This contributes to economical and social sustainable development, as well as to cohesion for trans boundary areas, which include administrative and territorial units from neighboring countries. A correct conceptual basis for the methodological approach to connectivity lies in the fact that the development of transportation systems, as integrated networks at different scales, is deeply changing their operation and the way they induce urban and regional development patterns. Overloaded transport corridors in the context of changing transportation flows are becoming an important issue for accessibility, impacting CBC indirectly, but harshly. Different modes of transport create different patterns of accessibility, with different influence in CBC accordingly. Throughout the present research, CBC European case studies, where connectivity-movement between cities, has been identified as a key factor for their territorial success, were assessed, described and analyzed. In the period of 2001–2006, improvements and further imbalances have occurred in accessibility development across regions and modes. Some signs indicate that the core-periphery pattern is slowly changing which leads towards an upgrade on the accessibility of places, regions and cities.